Physicochemical properties of rice bran oil-based oleogel system - Ng, Lorraine Ruo Yen (2023)
Oleogels are emerging novel alternatives for conventional solid fats in the food industry. However, the physicochemical properties of oleogels are still not yet fully established such that they can fully acquire the physiochemical properties of conventional solid fats. Moreover, due to the vast number of possible combinations and concentrations of organic solvents and structuring agents to produce oleogels which have yet to be fully explored, there is still no conclusive findings on the best formulation of oleogel as of today. Therefore, this study aims to evaluate the physicochemical properties of a particular combination of rice bran oil-based oleogels which are structured with beeswax and palm wax at different concentrations, along with the synergistic effects of both structuring agents. In this study, a total of 13 variations of oleogels were prepared at different wax concentration and combinations and their physicochemical properties were assessed: (i) 2% BW; (ii) 4% BW; (iii) 6% BW; (iv) 8% BW; (v) 10% BW; (vi) 14% BW; (vii) 1% BW 1% PW; (viii) 2% BW 2% PW; (ix) 4% BW 4% PW; (x) 6% BW 6% PW; (xi) 8% PW; (xii) 10% PW and (xiii) 14% PW. Synergistic effects from PW was observed in both thermal analysis (differential scanning calorimetry and slip melting point). All RBO oleogel samples exhibited shear thinning behavior at increasing shear rate and were found to portray more elastic iii than viscous properties. The type of wax and concentration of wax were also the major determining factors of the intensity and magnitudes of most of the parameters measured in the analysis carried out. The oxidative stability of the RBO oleogel samples were also found to be incompatible with that of commercial margarine used as a control, due to the presence of high amounts of unsaturated fatty acids in RBO oleogels. Microscopic studies showed that the microstructure of PW (small spherulitic crystals) was more dominant in hybrid wax oleogels than BW (needle-like crystals). From the colorimetry analysis, the color of the margarine control sample was also found to be significantly different from the RBO oleogel samples. OBC test results on the other hand indicated that there was no significant difference in the OBC values among all the RBO oleogel samples except for 1% BW 1% PW. Synergistic effects from both waxes were observed in textural analysis where harder hybrid wax RBO oleogels were produced in comparison to RBO oleogels gelled with a single oleogelator at the same concentration. Overall, two particular oleogels, namely BW4PW4 and BW6PW6 showed potential for further study to scrutinize the synergistic potentials of BW and PW in other physicochemical properties not done in the present study as synergism in RBO oleogels have shown to be a promising solution to complement the limitations of each type of wax when they are used to gel RBO alone.